2016
DOI: 10.1111/febs.13819
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into protein modification and sulfur mobilization activities of noncanonical E1 and associated ubiquitin‐like proteins of Archaea

Abstract: Here we provide the first detailed biochemical study of a noncanonical E1-like enzyme with broad specificity for cognate ubiquitin-like (Ubl) proteins that mediates Ubl protein modification and sulfur mobilization to form molybdopterin and thiolated tRNA. Isothermal titration calorimetry and in vivo analyses proved useful in discovering that environmental conditions, ATP binding and Ubl type controlled the mechanism of association of the Ubl protein with its cognate E1-like enzyme (SAMP and UbaA of the archaeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 67 publications
(92 reference statements)
1
29
0
Order By: Relevance
“…However, accurate indicators for the prognosis of HCC are limited. Consequently, there is an urgency to develop a novel biomarker for the prognosis of HCC.The ubiquitin system serves a critical role in numerous cellular events, including the cell cycle regulation, DNA repair, stress responses, metabolic homeostasis, organelle biosynthesis and apoptosis (16,17). A recent study demonstrated that the hepatitis C virus NS3 protein enhanced HCC cell invasion by promoting protein phosphatase magnesium-dependent 1A ubiquitination and degradation (18), which indicated degradation and ubiquitination of proteins were involed in …”
mentioning
confidence: 99%
“…However, accurate indicators for the prognosis of HCC are limited. Consequently, there is an urgency to develop a novel biomarker for the prognosis of HCC.The ubiquitin system serves a critical role in numerous cellular events, including the cell cycle regulation, DNA repair, stress responses, metabolic homeostasis, organelle biosynthesis and apoptosis (16,17). A recent study demonstrated that the hepatitis C virus NS3 protein enhanced HCC cell invasion by promoting protein phosphatase magnesium-dependent 1A ubiquitination and degradation (18), which indicated degradation and ubiquitination of proteins were involed in …”
mentioning
confidence: 99%
“…Haloferax volcanii LR03 ( Δsamp1 Δsamp2 Δsamp3 ΔmsrA ΔubaA ) carrying plasmid pJAM3010 (a plasmid encoding msrA-strepII under control of the P2 rrnA constitutive promoter) (Fu et al , 2017) or pJAM1209 (a plasmid encoding his 6 -ubaA under control of the P2 rrnA constitutive promoter) (Hepowit et al , 2016) or without carrying any plasmid…”
Section: [Background]mentioning
confidence: 99%
“…Escherichia coli Rosetta (DE3) (Novagen, Merck, catalog number: 70954-3) carrying plasmid pJAM3200 (a plasmid encoding msrA-strepII under control of T7 promoter) from the Maupin-Furlow lab (Fu et al , 2017) or plasmid pJAM1132 (a plasmid encoding flag-his 6 -samp2 under control of T7 promoter) from the Maupin-Furlow lab (Hepowit et al , 2016)…”
Section: [Background]mentioning
confidence: 99%
“…This is based on the observations that (i) the ncs6 gene homologs are widespread in archaeal genomes [8]; (ii) the deletion of the ncs6 homolog ( ncsA ) in Haloferax volcanii resulted in only non-thiolated tRNA Lys UUU [71]; (iii) Ncs6 homologs form complexes with the ubiquitin-like small archaeal modifier protein (SAMP), which has high structural homology to Urm1, in H. volcanii [72] and in M. maripaludis [51]; (iv) the H. volcanii E1-like protein UbaA activates SAMP in formation of a thioester intermediate [73]; (v) the deletion of either samp2 or ubaA in H. volcanii eliminated thiolated tRNA Lys UUU [52]; and (vi) the M. maripaludis Ncs6 homolog has a [3Fe-4S] cluster [46]. These findings suggest that both an Fe–S cluster containing Ncs6 homolog and an activated ubiquitin-like protein are required for s 2 U34 formation in Archaea.…”
Section: Fe–s Cluster-dependent and Independent Trna Thiolation Prmentioning
confidence: 99%